Caecal Perforation from Primary Intestinal Tuberculosis in Pregnancy - Soe Lwin; Nina Lau Lee Jing; Haris Suharjono; Mardiana binti Kipli; Tin Moe Nwe; Myat San Yi; Lucas Luk Tien Wee (Case Reports in Gastrointestinal Medicine)
The incidence of tuberculosis (TB) is rising worldwide, despite the efficacy of the BCG vaccination. Populations at greatest risk of contracting TB are migrant communities, as well as immunocompromised individuals. The diagnosis of extrapulmonary TB (EPTB) can often present as a diagnostic conundrum, due to its nonspecific and varied presentation, often mimicking inflammatory bowel disease or malignancy. We present a case of caecal TB in pregnancy, which resulted in caecal perforation, a right hemicolectomy, and severe preterm delivery. The aim of this case report is to discuss the diagnosis of extrapulmonary TB, as well as its subsequent management in pregnancy.